Short-term high-fat diet alters the mouse brain magnetic resonance imaging parameters consistently with neuroinflammation on males and metabolic rearrangements on females. A pre-clinical study with an optimized selection of linear mixed-effects models - Campillo, Basilio Willem; Galguera, David; Cerdan, Sebastian; López-Larrubia, Pilar; Lizarbe, Blanca (Frontiers in Neuroscience, 2022)
Introduction High-fat diet (HFD) consumption is known to trigger an inflammatory response in the brain that prompts the dysregulation of energy balance, leads to insulin and leptin resistance, and ultimately obesity. Obesity, at the same, has been related to cerebral magnetic resonance imaging (MRI) alterations, but the onset of HFD-induced neuroinflammation, however, has been principally reported on male rodents and by ex vivo methods, with the effects on females and the origin of MRI changes remaining unassessed. Methods We characterized the onset and evolution of obesity on male and female mice during standard or HFD administration by physiological markers and multiparametric MRI on four cerebral regions involved in appetite regulation and energy homeostasis. We investigated the effects of diet, time under diet, brain region and sex by identifying their significant contributions to sequential linear mixed-effects models, and obtained their regional neurochemical profiles by high-resolution magic angle spinning spectroscopy. Results Male mice developed an obese phenotype paralleled by fast increases in magnetization transfer ratio values, while females delayed the obesity progress and showed no MRI-signs of cerebral inflammation, but larger metabolic rearrangements on the neurochemical profile. Discussion Our study reveals early MRI-detectable changes compatible with the development of HFD-induced cerebral cytotoxic inflammation on males but suggest the existence of compensatory metabolic adaptations on females that preclude the corresponding detection of MRI alterations.